2015
DOI: 10.1126/science.1261093
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for Notch1 engagement of Delta-like 4

Abstract: Notch receptors guide mammalian cell fate decisions by engaging the proteins Jagged and Delta-like (DLL). The 2.3 angstrom resolution crystal structure of the interacting regions of the Notch1-DLL4 complex reveals a two-site, antiparallel binding orientation assisted by Notch1 O-linked glycosylation. Notch1 epidermal growth factor–like repeats 11 and 12 interact with the DLL4 Delta/Serrate/Lag-2 (DSL) domain and module at the N-terminus of Notch ligands (MNNL) domains, respectively. Threonine and serine residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
303
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(328 citation statements)
references
References 67 publications
11
303
0
3
Order By: Relevance
“…These findings are consistent with results of previous in vitro studies using purified ligand protein fragments showing that the presence of EGF2 and EGF3 in these fragments is essential for effective binding to, and activation of, Notch (Shimizu et al 1999;Andrawes et al 2013). Since the MNNL and the DSL domain of DLL4 (and most likely also of DLL1) are in direct contact with the ligand binding interface of the receptor (EGF 11 and 12) (Luca et al 2015), EGF2 and EGF3 could contribute to the direct interaction of ligand and receptor by binding to Notch adjacent to EGF 11 ( Figure 5B, b), which is consistent with the observation that additional EGF repeats outside the major ligand binding site of Notch receptors are essential for full Notch activation and function (Shimizu et al 1999;Hambleton et al 2004;Xu et al 2005;Cordle et al 2008b;Andrawes et al 2013). Such an interaction could not be observed by Luca et al (2015) since EGF repeats of Notch1 potentially involved in this interaction were not included in their study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These findings are consistent with results of previous in vitro studies using purified ligand protein fragments showing that the presence of EGF2 and EGF3 in these fragments is essential for effective binding to, and activation of, Notch (Shimizu et al 1999;Andrawes et al 2013). Since the MNNL and the DSL domain of DLL4 (and most likely also of DLL1) are in direct contact with the ligand binding interface of the receptor (EGF 11 and 12) (Luca et al 2015), EGF2 and EGF3 could contribute to the direct interaction of ligand and receptor by binding to Notch adjacent to EGF 11 ( Figure 5B, b), which is consistent with the observation that additional EGF repeats outside the major ligand binding site of Notch receptors are essential for full Notch activation and function (Shimizu et al 1999;Hambleton et al 2004;Xu et al 2005;Cordle et al 2008b;Andrawes et al 2013). Such an interaction could not be observed by Luca et al (2015) since EGF repeats of Notch1 potentially involved in this interaction were not included in their study.…”
Section: Discussionsupporting
confidence: 81%
“…Likewise, a fragment of human Jag1 encompassing the DSL domain and first three EGF repeats was shown to bind to fragments of human Notch1 encompassing EGF repeats 10-13 (Cordle et al 2008a), and deletion analyses of human DLL1 and DLL4 showed that the regions containing the MNNL to EGF3 were necessary and sufficient for full activation of Notch1 (Andrawes et al 2013). Recently, the structure of a complex of EGF repeats 11-13 of Notch1 with the N-terminal portion of DLL4 up to and including EGF2 was published, showing that EGF repeats 11 and 12 of Notch interact with the DSL and MNNL domains of the ligand, respectively, placing EGF1 and -2 outside the essential Notch interaction surface (Luca et al 2015).…”
mentioning
confidence: 99%
“…In our mass spectral analyses, we were particularly interested in determining which O-fucose sites were modified by Fringe because those sites should play important roles in the effects Fringe has on Notch. Recent structural studies on the ligand binding domain of mammalian Notch1 show that the O-fucose glycans on EGF12 directly interact with ligands upon binding (22,50). From the EIC analysis, we observed that Fringe elongates some sites more efficiently than others.…”
Section: Xxxx(s/t)cmentioning
confidence: 71%
“…3). Recent structure of Rat NOTCH1 EGF11‐13 in complex with its ligand DLL494 provides a basis to analyze the functional consequence of mutations at this region. Surprisingly, frequent mutations (10 out of 22) occur at cysteine positions (Table 1 and Fig.…”
Section: A Complete View Of Notch1 Mutations Across Sccsmentioning
confidence: 99%